Lexeme "Valjda" as an Exponent of Epistemic Modality - Stojanović, Milena S.; Parezanović, Tijana V.; Kovačević, Branka B. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper aims to describe the functional and semantic characteristics of the word valjda in the Serbian language. Corpus examples are used as a methodological tool for comparing the lexeme valjda to its closest synonym verovatno, with respect to their respective uses and meanings in sentence structure. Classifying the lexeme verovatno as an adverb/adjective in Serbian grammars is contrasts with assigning valjda to the category of particles. The fact that functional-semantic synonyms are categorized as different parts of speech points to fluid boundaries between word classes. The paper theoretically relies on the work of Jan Nuyts on epistemic modality, who argues that analyzing language in a radically functional manner is a prerequisite for discovering the underlying cognitive infrastructure of the mind. The position of the lexeme valjda on the epistemic scale-somewhere between the epistemic meanings of certainty and possibility, signalled by words such as certainly, definitely, undoubtedly i.e. maybe, might, possibly-is also discussed. Corpus analysis of examples showing valjda and its relation to negation reveals distinctive semantic features of the lexeme in question. Furthermore, collocations with modal verbs and intensifiers commonly associated with modal lexical items in the Serbian language are considered. In this respect, the lexeme valjda is shown to be similar to other (sentence) adverbs, especially those that modify sentence meaning in terms of epistemic modality. However, the lexeme’s inability to be intensified (i.e., amplified or reduced) by shifting its position on the epistemic scale indicates a similarity to the word možda. This shared characteristic may strengthen the argument for assigning valjda to the particle category